Exaptation in Physics and Materials Science - Zaiser, Michael; Zapperi, Stefano (Understanding Innovation Through Exaptation, 2020)
The biological theory of evolution has been used as a powerful analogy for the history of technological innovation. Here, we discuss how the concept of exaptation, which in the context of evolutionary biology describes the advantageous exploitation of existing traits for completely new functions, can be used to better understand what drives scientific progress in theoretical physics and materials science. The rapidly growing field of automatic materials discovery provides excellent examples of both adaptation and exaptation. Finally, we discuss how basic mechanisms resulting from long-term evolutionary histories—based both on adaptation and exaptation—can now be exploited to design new functional bio-inspired materials.<br
Keywords: Theoretical physics; Materials discovery; Bio-inspired materials; Machine learning